2016
DOI: 10.1039/c5cc08764c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a far-red fluorophore and its use as an esterase probe in living cells

Abstract: We report the synthesis of a new far-red fluorophore, 1,3-dichloro-7-hydroxy-2H-spiro[acridine-9,1'-cyclohexane]-2',5'-diene-2,4'-dione (DSACO), which was modified to make two esterase probes: DSACO-2-AME and DSACO-7-AME. Both probes act as "turn-on" substrates for esterases and lipases. DSACO-2-AME exhibited efficient esterase-activated fluorescence inside living cells and is a stable, far-red alternative for the widely-used fluorescein diacetate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
28
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 22 publications
2
28
0
2
Order By: Relevance
“…Chemical modification of DDAO arachidonate to reduce sPLA2 activation might reduce this observed background. Furthermore, use of fluorophores similar to DDAO, with longer emission wavelengths, might improve detection following systemic administration 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Chemical modification of DDAO arachidonate to reduce sPLA2 activation might reduce this observed background. Furthermore, use of fluorophores similar to DDAO, with longer emission wavelengths, might improve detection following systemic administration 49 .…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, an assortment of methods including immunology, chromatography, chemiluminescence, mass spectrometry and uorescence, have been reported for carboxylesterase detection. [15][16][17][18][19][20][21][22] Among them, uorescent probes for detecting carboxylesterase have become more and more attractive because of their advantages such as high sensitivity, selectivity and high temporal-spatial resolution. [23][24][25][26] For example, Zhou et al reported a new lysosome-targeted uorescence probe with emission 575 nm for uorescence sensing of carboxylesterase in live cells, sera and tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, previous work has clearly demonstrated the utility of acetoxymethyl (AM) ether groups for masking phenol functionalities within fluorophores. [23][24][25]33 The resulting AM-protected probes display low background fluorescence, high chemical stability, and are readily cleaved by cellular esterases producing a turn-on fluorescent probe for esterase activity. Based on our previous results, we also anticipated that the negatively charged phosphinate of NR 600 would prevent the fluorophore from entering cells.…”
mentioning
confidence: 99%